Citizen science can add value to Phytophthora monitoring: five case studies from western North America - Lanning, Kara K.; Kline, Norma; Elliott, Marianne; Stamm, Elizabeth; Warnick, Taylor; LeBoldus, Jared M.; Garbelotto, Matteo; Chastagner, Gary; Hulbert, Joseph M. (Frontiers in Environmental Science, 2023)
Phytophthora species are plant pathogens responsible for many notable biological invasions in agricultural, forests, and natural ecosystems. Detection and monitoring for invasive introductions of Phytophthora spp. is time and resource intensive. Development of citizen science detection and monitoring programs can aid in these efforts focused on reducing Phythophthora impacts. There are multiple methods for monitoring and detecting Phytophthora invasions suitable for citizen science approaches such as, leaf sampling, stream baiting or soil collections. Here we summarize five active projects in western North America where citizen scientists are aiding the monitoring and research efforts surrounding Phytophthora species and their impacts. Projects varied in scope, scale, methods, and capacity, but each project increased citizen scientists' abilities for surveillance and advanced detection or knowledge of Phytophthora species. Some projects were integrated with school programs, others involved hands-on training with small groups, and another approach invited mass participation from interested citizens. Overall, all projects had positive outcomes multiplied across education, monitoring, and research. Together these case studies demonstrate how citizen scientists can amplify surveillance efforts, advance baseline knowledge, and reduce the impacts of biological invasions.